2017
DOI: 10.1103/physrevb.95.245202
|View full text |Cite
|
Sign up to set email alerts
|

Migration mechanisms and diffusion barriers of vacancies in Ga2O3

Abstract: We employ the nudged elastic band and the dimer methods within the standard density functional theory (DFT) formalism to study the migration of the oxygen and gallium vacancies in the monoclinic structure of β-Ga 2 O 3. We identify all the first nearest neighbor paths and calculate the migration barriers for the diffusion of the oxygen and gallium vacancies. We also identify the metastable sites of the gallium vacancies which are critical for the diffusion of the gallium atoms. The migration barriers for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(83 citation statements)
references
References 62 publications
8
75
0
Order By: Relevance
“…A larger sampling resulted in the conclusion that these complexes exist lesser in quantity and smaller in intensity in comparison to Sn-doped β-Ga2O3. This is consistent with the expectations that the incorporation of Sn donors that drive the material more n-type simultaneously stimulates the formation of the compensating acceptor species like the 2V "# $ -Gai complexes [19,21,24] through the subsequent increase in vacancy concentration. Additionally, Sn may also incorporate as the cation interstitial, forming 2V "# $ -Sni complexes.…”
Section: Gasupporting
confidence: 91%
See 2 more Smart Citations
“…A larger sampling resulted in the conclusion that these complexes exist lesser in quantity and smaller in intensity in comparison to Sn-doped β-Ga2O3. This is consistent with the expectations that the incorporation of Sn donors that drive the material more n-type simultaneously stimulates the formation of the compensating acceptor species like the 2V "# $ -Gai complexes [19,21,24] through the subsequent increase in vacancy concentration. Additionally, Sn may also incorporate as the cation interstitial, forming 2V "# $ -Sni complexes.…”
Section: Gasupporting
confidence: 91%
“…This complex is lower in energy than the isolated vacancy, and acts as a deep acceptor. [19,21]. These DFT results have also been utilized in recent β-Ga2O3 defect studies using electron spin resonance [37,38] and infrared spectroscopy [39,40] to attribute the presence of proton irradiation induced defects and implanted O-H bonds to the same point defect complexes.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…showed that although PBE significantly underestimates the bandgap of the Ga 2 O 3 , it predicts identical density of states and line shapes to that calculated by using the HSE06 hybrid functional, which can predict the exact bandgap . Angle‐resolved photoemission spectroscopy and DFT studies agree that β‐Ga 2 O 3 is an indirect material with the CBM at Gamma and VBM at M(1/2 1/2 1/2 ) . The calculated indirect bandgap for the bulk structure is 2.15 eV, whereas the bandgap is narrowed down by 9 % to 1.955 eV for a clean (−201) surface and further decreases to 1.75 eV when the surface is hydrogenated (monolayer (ML)=0.25 coverage).…”
Section: Resultsmentioning
confidence: 71%
“…Several previous theoretical works have addressed the point defects. [8][9][10][11][12][13][14][15] On the experimental side, Electron Paramagnetic Resonance (EPR) provides one of the most powerfull methods to identify the chemical nature of defect centers. Several papers recently reported EPR centers in β-Ga 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%